Distribution Characteristics and Temporal Variation of Climate Comfortableness in the Yellow River Basin under the Background of Climate Change - Tian JIN; Caihong CHEN; Jinkui WU (Gaoyuan qixiang, 2025)
Climate comfortableness is the key factor that has impact in many fields， such as residents’ life quality， tourism development， and urban planning layout.The Universal Thermal Climate Index （UTCI is currently the most important and effective way to evaluate climate comfortableness at the international level.In-depth research on the climate comfortableness of the Yellow River Basin can not only fill the gap in the study of climate comfortableness in the Yellow River Basin area but also supplement a comprehensive understanding.Based on the results of climate zoning， the Yellow River Basin is divided into six sub-regions Using the reanalyzing data of ERA 5， the spatial distribution and temporal change of climate comfortableness in the Yellow River Basin from 1979 to 2022 were analyzed and discussed with the adoption of UTCI.The results show as follows： （1） From an overall perspective， the annual average UTCI value of the Yellow River Basin is 2.8 ℃， with a comfortable grade of coolness.The UTCI value is mostly in the cold zone and comfortable zone.The distribution of hot zone is relatively less.There is a large difference in UTCI distribution among the internal regions.Region I has a relatively longer duration of low temperature， and the area， with mild cold stress （coolness） and stronger cold stress （uncomfortable coldness）， is larger.Region II is mostly in the cold zone.Region III and Region IV are relatively close， and are dominated by “comfortableness” and “coolness”.The UTCI values in region V and region VI are at a higher level， but most areas are still in the comfortable zone.（2） In terms of the seasons， the four regions of III， IV， V， and VI have relatively extensive comfortable zones in spring and autumn， the overall comfortable area will be expanded in summer across the entire Yellow River basin， and the cold and uncomfortable zone will become dominant in winter， while the overall comfortable zone will be shrinked across the entire Yellow River basin.（3） The average UTCI in China as a whole has shown an overall upward trend from 1979 to 2022， with a change rate of 0.4 ℃·（10a）-1.The range of change in sub-regions is 0.14~0.85 ℃·（10a）-1.The annual UTCI change in the Yellow River basic shows a significant feature of west-high-east-low and north-high-south-low in the spatial distribution.（4） The level of climate comfortableness， taken as a whole， is mainly in the comfortable and slightly uncomfortable categories.The number of days in each of the six comfortable levels is as follows： 24 days （cold discomfort）， 126 days （slightly cold， discomfort）， 59 days （cool）， 131 days （comfort）， 19 days （slightly hot discomfort）， and 6 days （hot discomfort）.Region I and Region II have not been affected by the discomfort caused by heat.However， regions in the Yellow River basin， and regions of III， IV， V， and VI， are affected by slightly hot discomfort and the average duration in the slightly hot discomfort zone throughout the year is 19 days， 23 days， 24 days， 46 days， and 60 days respectively.